2015
DOI: 10.1007/s10750-015-2340-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanisms of coexistence between two globally important Pseudo-nitzschia (Bacillariophyta) species

Abstract: To understand the mechanisms leading to coexistence and exclusion, it is essential to establish information on the nutritional needs of species. We focused on the frequently coexisting Pseudo-nitzschia species, P. delicatissima and P. galaxiae, capable of forming blooms and producing domoic acid. We employed monoculture experiments to determine growth kinetic parameters important for understanding resource use (i.e. maximum specific growth rate, half-saturation coefficients for growth and cell quotas), and we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…A kainic acid analogue, domoic acid, produced by the diatom genus, Pseudo-nitzschia , acts as an intra and inter-species allelochemical, and is responsible for toxic algal blooms. Domoic acid is an excitotoxic amino acid that affects the central nervous system in vertebrates such as shrimp, and competitively inhibits the growth of other Pseudo-nitzschia species [ 17 , 18 ]. Similarly, ovatoxins and palytoxins produced by the toxic dinoflagellate protozoan, Ostreopsis , [ 19 ] act as allelochemical deterrents to neighbouring vertebrates, and can cause algal blooms.…”
Section: Antibacterial Compounds In Marine Algae and Their Functiomentioning
confidence: 99%
“…A kainic acid analogue, domoic acid, produced by the diatom genus, Pseudo-nitzschia , acts as an intra and inter-species allelochemical, and is responsible for toxic algal blooms. Domoic acid is an excitotoxic amino acid that affects the central nervous system in vertebrates such as shrimp, and competitively inhibits the growth of other Pseudo-nitzschia species [ 17 , 18 ]. Similarly, ovatoxins and palytoxins produced by the toxic dinoflagellate protozoan, Ostreopsis , [ 19 ] act as allelochemical deterrents to neighbouring vertebrates, and can cause algal blooms.…”
Section: Antibacterial Compounds In Marine Algae and Their Functiomentioning
confidence: 99%
“…In addition, cells may be more vulnerable during sexual reproduction, so domoic acid could act as a grazer deterrent: its production has been shown to increase in the presence of copepods (Harðard ottir et al 2015. Finally, different studies also showed an allelopathic effect of Pseudo-nitzschia or DA addition on different phytoplankton species (Lundholm et al 2005, Smeti et al 2015, Sobrinho et al 2017, Van Meerssche et al 2018). Higher DA production may therefore also represent an ecological advantage that could offset the growth arrest/decrease during sexual events in Pseudo-nitzschia blooms.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus plausible that negative effects to co-cultured target microalgae are not due to chemical interference but rather to the higher competitive ability of the focal species for the limiting resource [32] . Although it is possible to isolate the effect of allelopathy from resource competition by using either culture filtrate or cellular lipophilic extract of the focal species [24] , [33] , [34] , [35] , it is impossible to isolate the effect of resource competition from that of chemical interference in co-cultures [32] , [36] . This poses the necessity to investigate chemical interference in isolation, while carefully controlling for nutrient concentrations, as an essential step towards understanding how both processes act antagonistically or synergistically to sustain species co-existence and biomass.…”
Section: Introductionmentioning
confidence: 99%